Training Effects of the FIFA 11+ Kids on Physical Performance in Youth Football Players: A Randomized Control Trial - Carlos Pomares-Noguera; Francisco Ayala; Francisco Javier Robles-Palazón; Juan F. Alomoto-Burneo; Alejandro López-Valenciano; José L. L. Elvira; Sergio Hernández-Sánchez; Mark De Ste Croix (Frontiers Media S.A., 2018)
ObjectiveTo analyze the training effects of the FIFA 11+ kids on several parameters of physical performance in male youth football players.Materials and methodsTwenty-three youth players were randomized within each team into two groups (control vs. intervention). The intervention group performed the FIFA 11+ kids programme 2 times a week for 4 weeks; the control groups completed their normal warm-up routines. Thirteen physical performance measures {range of motion (hip, knee, and ankle joints), dynamic postural control (measured throughout the Y balance test), 20 m sprint time, slalom dribble with a ball, agility, vertical jumping height [counter movement jump (CMJ) and drop jump (DJ)], horizontal jump distance, accuracy when volleying a ball [measured throughout the Wall Volley test]} were assessed. All physical performance parameters were compared via magnitude-based inference analysis.ResultsSignificant between-group differences in favor of the FIFA 11+ players were found for dynamic postural control {anterior [mean and 90% confidence intervals (CI) = 1 cm, from −1.6 to 3.5 cm] and posteromedial (mean and 90% CI = 5.1 cm, from −1.8 to 12 cm) and posterolateral (mean and 90% CI = 4.8 cm, from 0.6 to 9.0 cm) distances}, agility run (mean and 90% CI = 0.5 s, from −0.9 to 0 s), vertical jump height [CMJ (mean and 90% CI = 3.1 cm, from 0.2 to 6.1 cm) and DJ (mean and 90% CI = 1.7 cm, from −0.5 to 3.9 cm)], and horizontal jump distance (mean and 90% CI = 2.5 cm, from −8 to 15 cm). The control groups showed better performance in 20 m sprint time (mean and 90% CI = −0.05 s, from −0.11 to 0.07) and wall volley tests (mean and 90% CI = 0.2, from −0.2 to 0.6) compared to the intervention group.ConclusionThe main findings of this study suggest that just 4 weeks of implementation of the FIFA 11+ kids produces improved physical performance compared with traditional warm-up routines in youth soccer players.